2012
DOI: 10.3126/njenthns.v2i2.6803
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Laryngeal Nerve Palsy After Thyroid Surgery and Literature Review

Abstract: Thyroid surgery is one of the common surgeries performed in head and neck region. Recurrent laryngeal nerve paralysis is one of the most frequent and serious complications after thyroid operation. Permanent nerve palsy may occur in 0% to 2.1%, with an average of approximately 0.5% to 1%. Temporary palsy varies from 2.9% to over 10% 1 . The right-sided nerve is at higher risk due to its wide anatomical variation as compared to the left one. This complication rate can be minimized by accurate anatomical knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…13 In contrast, the study of Dutta et al reported that more than half underwent lobectomy while the rest were distributed among total thyroidectomy, subtotal and completion thyroidectomy, with about 13% RLNI. 14 The majority were patients who underwent total thyroidectomy; 3x higher than patients who underwent subtotal thyroidectomy and 1.5x higher than those who underwent lobectomy. 14 Our current study attempted to determine the association between type of surgery and the presence of RLNI.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…13 In contrast, the study of Dutta et al reported that more than half underwent lobectomy while the rest were distributed among total thyroidectomy, subtotal and completion thyroidectomy, with about 13% RLNI. 14 The majority were patients who underwent total thyroidectomy; 3x higher than patients who underwent subtotal thyroidectomy and 1.5x higher than those who underwent lobectomy. 14 Our current study attempted to determine the association between type of surgery and the presence of RLNI.…”
Section: Discussionmentioning
confidence: 93%
“…14 The majority were patients who underwent total thyroidectomy; 3x higher than patients who underwent subtotal thyroidectomy and 1.5x higher than those who underwent lobectomy. 14 Our current study attempted to determine the association between type of surgery and the presence of RLNI. However, there was no significant association found between these two variables.…”
Section: Discussionmentioning
confidence: 93%